FEATURES AND ADVANTAGES OF ELECTRONIC TEXTBOOKS IN THE TEACHING OF ASTRONOMY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The role of modern Information Technology in the creation of information educational resources for independent education in the current period is incomparable. In independent education, modern information technologies i.e. educational and methodological materials created on the basis of computer software, including the main purpose of using electronic textbooks is to form a modern information and educational style, increase the efficiency, quality and unity of the educational process through the use of modern information and pedagogical, information and computer technologies, widely use of modern educational resources in.